The Effect of Innovation and Marketing Mix Toward Brand Image and Usage Decision in Online Food Delivery Services Industry - Putri Dhika Savitri; Diah Krisnatuti; Sufrin Hannan (APMBA (Asia Pacific Management and Business Application), 2020)
Online food delivery service (OFD) is created as a service innovation that combines the usage of technology and electronic systems. Many brand present caused increasingly fierce competition between similar companies in one industry due to wider customers alternative selection. OFD companies need to implement innovation and a marketing mix to create a strong brand image. This study aims to analyze the effect of innovation and marketing mix on usage decisions through brand image through the development of five hypotheses. Data were collected by distributed online questionnaires to 292 respondents with 15 brands of OFD services that have been used in the last three months. Data analysis used the Structural Equation Modeling (SEM) method with Lisrel 8.80 software and descriptive analysis with SPSS ver 25.. The results showed that the marketing mix had a significant effect on brand image, and the innovation and marketing mix had a significant effect on usage decisions. Meanwhile, innovation has no significant effect on brand image and brand image has no significant effect on the decision to use an online food delivery service. The implication of this study is to improve marketing strategies by expanding the coverage area and developing innovations by creating a different uniqueness from the competitors.